Comparison of iron-sucrose with ferric carboxymaltose for treatment of postpartum iron deficiency anaemia - Vijan, Tanya S.; Mane, Suwarna; Kumar, Sushil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Anaemia is a major public health problem worldwide. Haemoglobin (Hb) cut-off in anaemia should be taken as 11 gm/dl in the first and third trimester and 10.5 gm/dl in the second trimester, and a post-partum Hb of 10.0 gm/dl. The aim of the study is to compare the efficacy of iron-sucrose versus ferric carboxymaltose (FCM) in the treatment of postpartum anaemia. Methods: A prospective randomized interventional study of 132 post-partum females was conducted at a tertiary care hospital, over a 6-month period. Post-partum females delivered via normal vaginal delivery or caesarean section with Hb levels of above 7 gm/dl and below 9.9 gm/dl were randomized into 2 groups. Iron deficit calculated, in mg, according to Ganzoni’s formula. One group received intravenous FCM – 500 mg in 250 ml normal saline (NS) over 30 minutes and the other received intravenous iron sucrose - each ampoule containing 200 mg in 100 ml NS over 30 minutes up to a maximum dose of 1000 mg. Follow up done after 15 days, 4 weeks and 6 weeks. The data was tabulated and compared using statistical analysis. Results: At a 4 and 6 weeks follow up, the mean rise in hemoglobin (Hb) of group A (1.4 g/dl) was significantly greater than that of group B (0.89 g/dl). Conclusions: The study concludes that thought efficacy of drugs is similar, injection FCM shows a prompt rise in Hb, allows a higher dose to be dispensed in a single seating and is more significant in improving quality of life over a period of time even though it has a marginally higher cost.